The built environment: pit-huts and houses in the Neolithic - Bailey, Douglass W. (Documenta Praehistorica, 1999)
Among the major changes which emerged in southeastern Europe after 6500 BC, one of the most significant was that people began to build ther social environments. Two main types of architectuer were used: pits-huts and surface-level structures. This paper examines the character of these two forms of bulidinsg and suggests that they represent important differences in community structure and ogranization. Examples are drawn from three sites, divostin (phases I and II), Usoe and Ovcharovo-gorata.
Keywords: jugovzhodna Evropa; neolitik; archaeology; arheologija; arheološke najdbe; socialno okolje; arhitektura; architecture; naselbine